BIMBINGAN TEKNIS PEMBUATAN APLIKASI GOOLE FORM UNTUK MENINGKATKAN KOMPETENSI GURU MIN 1 KETAPANG - Supriadi, Suoriadi (Universitas Tanjungpura, 2021)
The Implementation of Practical Assistance as an Effort to Enhance Teacher Competence in Optimizing Goole Form Application for Online Learning at Madrasah Ibtidaiyah Negeri (Islamic State Elementray School) 1 Ketapang Academic Year 2020/2021.The Implementation of Practical Assistance as an Effort to Enhance Teacher Competence in Optimizing Goole Form Application for Online Learning at Madrasah Ibtidaiyah Negeri (Islamic State ElementraySchool) 1 Ketapang Academic Year 2020/2021. The purpose of this study is to to develop teacher’s competence in bulding Google Form to improve the quality of learning and assessment. This research is a School Action Research which consists of 2 cycles, with the participatory observation from 15 teachers. Each cycle entails of planning, implementing, observing and reflecting. Based on the results of predetermined steps related to the research, there is an improvement in teacher ability compares before practical assessment is implementedand after it is implemented. The competence of teachers in making Goggle Form applications before practical assessment activities is in the range of values of 28% with the criterion for the score is Less. 2) Teacher’s competence in optimizing the Google Form application after the first stage reached values of 68% of satisfactory criteria. As in advance, after the second stage is practically completed, the score reached 86%, determined as more satisfactory criteriacompared from the previous stage.